Factors influencing child mortality in Bangladesh and their implications for the national health programme - M. Kabir; Ruhul Amin (Asia-Pacific Population Journal, 1993)
The Government should consider strategies to reduce poverty, expand schooling, particularly for girls, and help to strengthen women’s ability to care for their families.